Detoxification of Steam-Exploded Corn Stover Prehydrolyzate with Organobentonite Enhances Ethanol Fermentation by Pichia stipitis - Chenhuan Lai (BioResources, 2016)
The inhibitors derived from degradation of lignocellulose have adverse impacts on fermentation, which is considered to be a fundamental problem in bioethanol production. Fermentation of steam-exploded corn stover prehydrolyzate by Pichia stipitis showed that phenolic compounds had much higher inhibitory effects than weak acids and furan at high fermentation pH. Two types of organobentonite (cetyltrimethylammonium (CTMA)- and benzyltrimethylammonium (BTMA)-modified bentonite) were used to remove phenolic compounds in prehydrolyzate. The effectiveness of organobentonite treatment was evaluated by ethanol fermentation, which indicated that the organobentonite treatment improved the fermentability substantially, even though a noticeable difference was found in the phenol removal by the two organobentonites. Without organobentonite treatment, the sugar utilization ratio was only 68.1%, and the produced ethanol was 15.36 g/L. After CTMA- and BTMA-bentonite treatment, the sugar utilization ratios were beyond 95%; meanwhile, the ethanol production increased by 45.5% and 42.8%, respectively. This indicated that organobentonite treatment was a potential detoxification method.